Africanismo e arabismo no relato histórico escolar : Espanha, 1939-1956 - Monserrat, David Parra (2017)
An Africanist discourse of Spanish-Arabic brotherhood became institutionalized during the 1940s and early 1950s in Spain. Among other things, this discourse was used to legitimize the colonial presence in Morocco and to achieve the international support of the Arabic countries. Nevertheless, Francoist Africanism showed discursive plurality that raised deep contradictions between theory officially defended by the regime and spread abroad and discourses for domestic consumption. In this article, this discursive plurality is analized through the study of educational materials used in schools in peninsular Spain and in the Spanish Protectorate of Morocco.